Plan de marketing para el gimnasio “Bettos gym” del cantón Buena Fe, año 2015 - Murrieta Arroyo, Karla Joshelyn (2016)
This study was conducted in a company dedicated to offer service fitness training for development of this project is set to study the issue of implementation of a marketing plan for the gym "GYM BETTO`S" Canton Good Faith, 2015 . The main problem encountered in the gym is in the lack of basic technology and lack of training instructors, this allows the level of affluence of customers is limited because they are not motivated to perform basic exercise routines the rustic infrastructure shown in gyms, which in turn limits the acquisition of new customers. The main objective of this project is to implement a marketing plan for greater positioning gym "Betto`s Gym" main objective of this specific objectives expressed in keywords then emerge: situational analysis, market research, strategies marketing and action plan and budgeting. Those raised strategies to be developed for improving business activity gym include: designing promotional packages aimed at increasing the market share of the gym; advertising campaigns through media such as ATL and BTL; price-quality design strategies to build customer loyalty. The budget required for the implementation of this project is $4,895 and this from an economic point of view an attractive, accessible and sustainable value to the gym run the marketing plan proposed.